(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Housing development in Šárka’s valley is situated in former brickworks – borrow pit for brick-clay. On its north side the borrow pit cutting is up to 8m high with main road on top. This slope was suffering from progressive landslide mainly due to weathering and surface erosion. The reclamation works proposed and afterwards executed consisted of stabilizing the slope by combination of soil nailing and connecting reinforced slope with surcharge bench at its toe. The final reinforced soil structure nicely merged into the surrounding environment.